Estudio de las comidas típicas para la innovación de rutas gastronómicas en la Ciudad de Riobamba - Salazar Cerda, Geovanna Isabel (2026)
The research is titled "Study of Typical Foods for the Innovation of Gastronomic Routes in the City of Riobamba." It mainly studied the most representative traditional foods and identified the restaurants included in the research, either because of their age or recognition. It is essential to note that this project was carried out in conjunction with the owners of food and beverage establishments that serve typical fare. Twenty-six establishments serving typical cuisine were selected for surveys that included key questions designed to elicit brief, simple answers. The following research is descriptive and exploratory, with a non-experimental, cross-sectional design. The results obtained were used to test hypotheses through descriptive verification. A proposal was developed based on the establishments that sell typical food in Riobamba city and how they can be innovated.